Regression Analysis in Auditing: A Comparison of Alternative Investigation Rules - Kinney, William R.; Salamon, Gerald L. (Journal of Accounting Research, 1982)
William R. Kinney, Jr., Gerald L. Salamon, Regression Analysis in Auditing: A Comparison of Alternative Investigation Rules, Journal of Accounting Research, Vol. 20, No. 2, Part I (Autumn, 1982), pp. 350-366